Antimicrobial Resistance and Molecular Epidemiology of Staphylococcus aureus from Hunters and Hunting Dogs - Silva, Vanessa (2022)
This work was funded by the R&D Project CAREBIO2: Comparative assessment of antimicrobial resistance in environmental biofilms through proteomics—towards innovative theranostic biomarkers, with reference NORTE‐01‐0145‐FEDER‐030101 and PTDC/SAU‐INF/30101/2017, financed by the European Regional Development Fund (ERDF) through the Northern Regional Operational Program (NORTE 2020) and the Foundation for Science and Technology (FCT). This work was supported by the projects UIDB/CVT/00772/2020 and LA/P/0059/2020 funded by the Portuguese Foundation for Science and Technology (FCT). Publisher Copyright: © 2022 by the authors.